DESAIN KONVERTER BOOST DENGAN METODE KECERDASAN BUATAN BERBASIS MIKROKONTROLER STM32F103C8 - Denny Irawan (E-Link: Jurnal Teknik Elektro dan Informatika, 2020)
Energy conversion is needed to serve load characteristics according to consumer needs. Some of the human energy conversion techniques to date include: AC to DC (Rectifier), AC to AC (AC Controller), DC to AC (Inverter), DC to DC (Chopper).The use of electromechanical switching has begun to be reduced or even abandoned and replaced by electrical switching which has very high switching speeds.The energy conversion technique also includes the regulation of the output voltage produced by a converter so that current research is leading to the design of a reliable converter.Boost Converter is a converter that functions to regulate and increase the output voltage of the source voltage by setting its duty cycle.The optimal duty cycle value to produce the output voltage that is in accordance with the target, can be determined using the Flower Pollination (FPA) algorithm, together with the current sensor as feedback, and then controlled by the STM32F103C8 Microcontroller.